Effects of flocculants on in–situ recycling potential of waste EPB shield muck with residual foams - Yao Lu; Ming Huang; Jim S. Shiau; Fengwen Lai; Liqian Peng (Soils and Foundations)
The in–situ recycling technique offers a promising solution for the efficient management of the escalating volumes of waste muck or slurry generated during shield tunneling. While foam is extensively utilized for soil conditioning in earth pressure balance (EPB) tunneling, the effects of organic and inorganic flocculants on the in–situ recycling potential of waste EPB shield muck containing residual foams remain underexplored. To bridge this gap, laboratory experiments were conducted using four flocculants: cationic polyacrylamide (CPAM), nonionic polyacrylamide (NPAM), anionic polyacrylamide (APAM), and polyaluminum chloride (PACL), with an enhanced flocculation and press–filtration apparatus. The defoaming–flocculation–dewatering behavior of waste EPB shield muck was systematically investigated by evaluating key parameters, including residual foam height, defoaming ratio, antifoaming ratio, total suspended solids, turbidity, moisture content, and zeta potential, while accounting for both muck dry mass and fines content. Moreover, the microscopic structure of flocculates and filter cakes was characterized using nanoparticle size analysis and scanning electron microscopy. The experimental results reveal that CPAM exhibits constrained flocculation and dewatering efficiency, primarily attributed to diminished charge neutralization resulting from residual anionic surfactants. In contrast, PACL demonstrates superior dewatering performance compared to NPAM and APAM, but exhibits the lowest flocculation and foam–suppression efficiency. Additionally, a consistent linear negative correlation is identified between the flocculation and dewatering indices of EPB shield muck, independent of the flocculant type, whether organic or inorganic.